2020
DOI: 10.3341/kjo.2019.0109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Small Incision Lenticule Extraction in Myopia: Study of Vector Parameters and Corneal Aberrations

Abstract: Since Jose Barraquer invented keratomileusis for correction of high myopia in 1949, researchers have combined keratomileusis with excimer laser surface ablation to develop one of the most commonly used laser corneal refractive surgery techniques, laser in situ keratomileusis (LASIK) [1]. Creation of a corneal flap allows early visual recovery, less discomfort, and reduced stromal inflamma-Purpose: To investigate clinical outcomes of small incision lenticule extraction (SMILE) including vector parameters and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, both mentioned studies had lower preoperative SE and astigmatism compared to our study. 15,19 These results show that the SMILE procedure achieves good outcomes in the correction of myopia, although greater preoperative astigmatism results in higher SE outcomes. In terms of stability, a 10-year follow-up study of SMILE reported a regression of 0.30 D in SE.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, both mentioned studies had lower preoperative SE and astigmatism compared to our study. 15,19 These results show that the SMILE procedure achieves good outcomes in the correction of myopia, although greater preoperative astigmatism results in higher SE outcomes. In terms of stability, a 10-year follow-up study of SMILE reported a regression of 0.30 D in SE.…”
Section: Discussionmentioning
confidence: 78%
“…These results are in accordance with the results of previous studies. 12,15,19 Vector analysis demonstrates that the proportional loss of the flattening effect is 1.5% when treatment is misaligned by 5 degrees and as high as 50% when 30 degrees. 26 Therefore, the astigmatic magnitude and treatment alignment both affect the outcomes of astigmatism correction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that despite increases in spherical aberrations, coma, trefoil, and total HOAs after SMILE, there is no clear association with visual symptoms. [25][26][27][28] Both LCVA and contrast sensitivity are important measures of quality of vision. Despite increases in HOAs, our study showed LCVA and contrast sensitivity may fluctuate in the early postoperative period after the SMILE procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that despite increases in spherical aberrations, coma, trefoil, and total HOAs after SMILE, there is no clear association with visual symptoms. 25–28…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In 2018, the US FDA approved SMILE for the treatment of myopic astigmatism from >−0.50 to ≤−3.00 diopters (D), 7 and the use of SMILE for this indication has since been further investigated. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Previous studies on the treatment of astigmatism with SMILE have found that it is safe and effective, but these studies were conducted outside of the United States. Our study will assess a single site's initial experience with SMILE for the treatment of myopic astigmatism and compare outcomes with FDA results and published literature.…”
Section: Introductionmentioning
confidence: 99%